Lignin alkali regulated interfacial polymerization towards ultra-selective and highly permeable nanofiltration membrane - Wentian Zhang; Shanshan Zhao; Haiyun Li; Cunxian Lai; Shangwei Zhang; Wu Wen; Chuyang Y. Tang; Fangang Meng (Nature Communications)
Abstract Thin-film composite polyamide (TFC PA) membranes hold promise for energy-efficient liquid separation, but achieving high permeance and precise separation membrane via a facile approach that is compatible with present manufacturing line remains a great challenge. Herein, we demonstrate the use of lignin alkali (LA) derived from waste of paper pulp as an aqueous phase additive to regulate interfacial polymerization (IP) process for achieving high performance nanofiltration (NF) membrane. Various characterizations and molecular dynamics simulations revealed that LA can promote the diffusion and partition of aqueous phase monomer piperazine (PIP) molecules into organic phase and their uniform dispersion on substrate, accelerating the IP reaction and promoting greater interfacial instabilities, thus endowing formation of TFC NF membrane with an ultrathin, highly cross-linked, and crumpled PA layer. The optimal membrane exhibited a remarkable water permeance of 26.0 L m-2 h-1 bar-1 and Cl-/SO4 2- selectivity of 191.0, which is superior to the state-of-the-art PA NF membranes. This study provides a cost-effective scalable strategy for fabricating ultra-selective and highly permeable NF membrane for precise ion-ion separation and small organic compounds removal.